Mouse models of myocardial infarction: comparing permanent ligation and ischaemia-reperfusion - De Villiers, C; Riley, PR (The Company of Biologists, 2020)
Myocardial infarction (MI) is a disease of major consequence in the modern world, causing permanent, irreversible damage to the heart. Survivors are at risk for developing further cardiovascular pathologies such as heart failure. Further study of MI injury is crucial to improve the understanding and treatment of the post-MI heart. The most commonly used model for MI in vivo is surgical ligation of the left anterior descending coronary artery (LAD). There are two predominant approaches: permanent ligation (PL), where the LAD is permanently occluded with a suture, or ischaemia-reperfusion (IR), where the LAD is temporarily occluded before removing the suture to restore blood flow and tissue reperfusion. PL results in the majority of the area at risk becoming infarcted, leading to significant apoptotic cell death and a large scar. Conversely, IR salvages some of the area at risk; thus, the scar is smaller and includes reperfusion injury, an additional, albeit smaller, second wave of necrotic damage. PL may be a more appropriate model choice for studies of heart tissue injury and wound healing, owing to the larger, more consistent infarcts, while IR enables the study of reperfusion injury. Both are clinically relevant, and the choice of model depends upon the precise pre-clinical research questions to be addressed.